Hydrogen-stimulated changes of properties of silver-porous silicon interfaces - Dzhafarov, TD; Omur, BC; Allahverdiev, ZA (ELSEVIER SCIENCE BV, 2001)
Electrical characteristics of Ag-PS interfaces under ambient humidity were investigated. The humidity-voltaic effect, i.e. the generation of open-circuit voltage in Ag-PS interface in humid atmosphere (up to 200 mV at 90% relative humidity) is discovered. Humidity-stimulated voltage generation is mainly caused by hydrogen component of water-vapour of ambient. The possible mechanism related with H-stimulated generation of voltage in Ag-PS interface is suggested. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: metal-semiconductor interfaces; silver; hydrogen atom; silicon; PHOTOLUMINESCENCE; WATER; Chemistry; Physics